Efeito do extrato etanólico de Gochnatia polymorpha (LESS.) e suas frações em linhagem celular de hepatocarcinoma HepG2 - Bastos, Matheus Scherer (2020)
Gochnatia polymorpha (Less) (Asteraceae) is a plant popularly known as Cambará and its extracts have been pointed out as a therapeutic alternative in several diseases, including inflammatory disorders. The aim of this study was to evaluate the potential therapeutic effect of ethanolic extract of G. polymorpha and its fractions (FI - Dichloromethane 90%; Methanol 10%; FII - Methanol 100%; FIII - Methanol 80%) on hepatocellular carcinoma (HepG2) cellular line. Cell proliferation was evaluated by the trypan blue exclusion counting method and the clonogenic assay. Cellular toxicity was analyzed by the release of the enzyme lactate dehydrogenase (LDH) by the cell. Cell senescence analysis was performed by nuclear morphological assessment (NMA) technique. Flow cytometry was also used to verify mechanisms related to cell death. Production of free radicals was assessed with the DCFH-DA oxidation sensitive reagent. The phenolic composition of the ethanolic extract and its fractions was characterized by HPLC. The results showed that ethanolic extract and its fractions decreased cell proliferation without causing necrosis, as well as decreasing survival of remaining cells after treatment. The analysis by flow cytometry did not reveal cell death by apoptosis or necrosis. Nevertheless, our findings demonstrated that the ethanolic extract and its fractions caused an increase in cellular senescence, activated by the p16 route, inhibiting the CCDN1 and CDK4 genes. An increase in autophagy was also demonstrated, except in the cells treated with FI fraction. It was also determined that cell senescence was triggered by production of free radicals. The phenolic compounds identified in the extract and fractions were hydroxybenzoic acid, coumaric acid, chlorogenic acid and gallic acid, varying in proportion according to the extract. We conclude that the ethanol extract of G. polymorpha and its fractions have an antiproliferative effect on HepG2 cells through the induction of autophagy and senescence driven by the oxidative stress. This effect might be related to the presence of hydroxybenzoic and chlorogenic acids, since both compounds are reported to induce ROS in neoplasms, being a potential alternative for the treatment of hepatocarcinoma.